Insuficiência pancreática exócrina em usuários de sorafenibe para tratamento do carcinoma hepatocelular - Peixoto, Samille Souza (2019)
Hepatocellular carcinoma is the most common primary liver neoplasm. It is an aggressive aggressive carcinoma, with associated high mortality. In advanced stages, systemic systemic therapy with sorafenib is the only option available. At early or intermediate stages, the use of this drug is considered as an alternative in case failure of the first option. Sorafenib has a broad spectrum of side effects described in the literature, and the association between its use and the onset of diarrhea is frequent. frequent association between its use and diarrheal symptoms. The aim of this study was to evaluate the exocrine exocrine function of the pancreas of these patients, in order to establish a possible association association between diarrheal symptoms after the introduction of sorafenib and the development of exocrine pancreatic insufficiency. The study was divided into two parts with distinct methodologies: the first, retrospective and qualitative, was second, cross-sectional and quantitative, consisted of the laboratory measurement of in the laboratory measurement of fecal elastase and SUDAM III. We included HCC patients taking sorafenib in the state of Sergipe were included. The exocrine exocrine pancreatic function was assessed by the dosage of fecal elastase, adopting 200 mcg/g of feces as the lower limit of normality. We had a total sample of seven total of seven patients, among whom five (71.5%) had diarrhea. Values below the minimum were found in two patients studied, with corresponding values of 39 mg/g and 112 mg/g. values of 39 mg/g and 112 mcg/g of feces, compatible with severe severe pancreatic insufficiency and mild to moderate pancreatic insufficiency respectively. The remaining patients had elastase >200 mcg/g. Thus, this study showed that patients taking sorafenib for the treatment of HCC may present decreased levels of fecal elastase translating to exocrine pancreatic exocrine pancreatic insufficiency, justifying the onset of diarrhea in this population